انگریزی ادب کو 'پروفیم'(نعت)کا تحفہ دینے والے شاعر: خان حسنین عاقبؔ - Ansar, Dr. Nasir ud Din (Zoraiz, 2023)
Poetry is that part of literature which ornaments the words and expressions a writer goes through. It is also a medium of expressing one's emotions and feelings. The endeavour of trying to wade through the untrodden path of taking up a new and so far untouched topic is a noteable effort. The theme and topic of my under-writing paper is a genre of literature which is struggling to be established as a permanent genre of poetry in English. An erudite writer and a gifted poet of Urdu and English Mr. Khan Hasnain Aaqib hails from India. He is basically a born poet but his inquisitiveness has inspired him to coin a new term for the poem denoting the praise of the holy prophet Hazrat Muhammad (p.b.u.h).There is an already well established genre of poems in other languages such as Arabic, Persian and Urdu along with some more langauges. This is called NAAT. Hasnain Aaqib coined to term 'Prophiem' for NAAT which seems a welcome-addition to the glossary and lexicon. This article focuses on the various aspects of the coinage of the term Prophiem as well as the post-introduction reactions of the writers and poets from around the world. The effort has been made to sum up a well researched and well collaborated article to give the impression that the coinage of the term was a long-awaited endeavour and innovation as far as the lexicon of constructive and reformative poetry is concerned. Hasnain Aaqib's innovative gesture seems to have been approved by a good number of poet laureates from the arena of literature and poetry. This paper is also an effort to initiate a constructive and formative dialogue about the Prophiem and the poets who somehow shy aways from organizing themselves as Prophiemist or prophiem writers in absence of a well documented institution and platform.